Bleeding versus Clotting: A Complex Case of a Large Fibroid Uterus Causing Menorrhagia and a DVT - Sangeeta Ramanan; Jude Chapman-Wardy; Roy Watson (Case Reports in Obstetrics and Gynecology)
A 43-year-old woman presented with severe anaemia secondary to menorrhagia. Pelvic ultrasound showed a large intramural posterior fundal fibroid. Hysteroscopy showed the fibroid distorting the endometrial cavity, precluding Mirena® device insertion. As she was initially hesitant to have a hysterectomy, medical management with the oral contraceptive pill (OCP) and tranexamic acid was instituted, with good effect. Months later, after a long road trip, she presented with left leg swelling, and a Doppler ultrasound confirmed an extensive deep vein thrombosis (DVT). She was commenced on warfarin for anticoagulation but presented again with menorrhagia precipitated by overanticoagulation. After initial stabilization with multiple blood transfusions and reversal of anticoagulation, the warfarin was ceased in favour of enoxaparin and she underwent inferior vena cava (IVC) filter insertion prior to a total abdominal hysterectomy. Mass effect from large uterine fibroids can cause venous thromboembolism (VTE). A duplex ultrasound of the lower limbs if a woman presents with a large fibroid could identify asymptomatic DVTs in such women. A prehysterectomy IVC filter would then reduce their risk of postoperative pulmonary embolism. Medical management of menorrhagia with procoagulants should be avoided for management of menorrhagia in such women given their higher risk of developing VTE.